PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN PROFITABILITAS TERHADAP EARNINGS RESPONSE COEFFICIENT PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2014-2018 - Yuniar Sarahwati; Iwan Setiadi (Kompartemen : Jurnal Ilmiah Akuntansi, 2021)
ABSTRACTThis research was conducted at property and real estate companies listed on the Indonesia Stock Exchange period 2014-2018. The sample was determined using purposive sampling method. The samples obtained was 30 companies with 150 observations. The data analysis method used is multiple linear regression analysis. The results of this study indicate that simultaneously company size, leverage and profitability have a significant effect on the earning response coefficient. While partially proves that firm size has no effect on earnings response coefficients, leverage has a significant negative effect on earnings response coefficients and profitability has a significant positive effect on earnings response coefficients. This research is expected to be useful for investors.Keywords: Firm size, leverage, profitability, earnings response coefficient